Experimental investigation into high strength S690 cold-formed circular hollow sections under compression. (July 2022) - Hu, Yi-Fei; Xiao, Meng; Chung, Kwok-Fai; Ban, Huiyong; Nethercot, David A.
Abstract: This paper presents an experimental investigation into the structural behaviour of both stocky and slender columns of high strength S690 cold-formed circular hollow sections (CFCHS) under compression. CFCHS are readily fabricated with cold-bending and welding on S690 steel plates, and these CFCHS are considered to behave similarly to those of hot-finished circular hollow sections. A total of 16 columns of S690 CFCHS were tested under compression, and these included eight stocky columns and eight slender columns with four different cross-section dimensions were tested. Tensile tests on typical curved coupons were also conducted to determine mechanical properties of these CFCHS while the sectioning method was employed to measure their residual stresses. All the stocky columns were found to have failed in material yielding in the sections while all the slender columns were found to have failed in overall buckling together with apparent plastic local buckling in the sections. The measured resistances of these columns of S690 CFCHS are then compared with those predicted resistances according to the current design rules given in EN1993–1. It is demonstrated that these design rules are effective to predict cross-section resistances of those stocky columns, and rather conservative to predict member resistances of those slender columns. The test results presented in the experimental investigation provide scientific data on their resistances for subsequent numerical investigations and design development for effective design rules. Graphical abstract: Unlabelled Image Highlights: Cold-formed circular hollow sections of S690 steels were fabricated and tested. 8 stocky and 8 slender columns of S690 CFCHS were tested under compression. Residual stresses within these CFCHS were measured and presented. Load-deformation characteristics of these CFCHS up to failure were obtained. Applicability of design rules given in EN 1993–1 on S690 CFCHS were assessed.